Genetic characterization of 27 Y-STR loci in the native population of Ashaninka from Peru. (December 2015) - Tineo, D.H.; Loiola, S.; Paredes, F.V.; Noli, L.R.; Amaya, Y.C.; Simão, F.; Carvalho, E.F.; Gusmão, L.
Abstract: The South American country of Peru is composed by a highly admixed population, with Native American, European and African genetic contributions. Some Native American groups in Peru underwent low admixture with Europeans or Africans and they have kept much of their culture and their original language. In this work we have studied one of these groups called Ashaninka, for the 27 Y chromosome specific STR loci that were included in the recently released YFiler Plus kit. The samples have been collected from 58 unrelated males belonging to 41 different communities located in the margins of the Amazonian rivers Pichis and Palcazú, in the district of Puerto Bermúdez, Pasco region, Peru. A high Y-STR haplotype diversity was found (1.0000 ± 0.0022) with all haplotypes being unique in the studied sample. Two markers that usually present a high diversity in European populations showed very low values of diversity in the Ashaninka Native Americans, namely the DYS635 (Het = 0.2263) and DYS437 (Het = 0.1325). On the other hand, the DYS438 showed a much higher diversity in Ashaninka (Het = 0.6582) group than that usually found in European populations. Apart from the multi-loci markers DYS385 and DYF387S1, more than one allele was also observed in one sample for DYS518 locus. This study represents the first report of haplotype frequencies for the YFiler Plus markers' set in a Native American population, showing a high diversity of haplotypes and, therefore, demonstrating their usefulness in forensic identification cases.